Heroines of the French epic : a second selection of chansons de geste - Newth, Michael A. (Woodbridge, Suffolk : D.S. Brewer, 2014)
The epic tales of medieval France, called chansons de geste, or "songs of deeds", provided the chief means of cultural and imaginative expression in the French language for over one hundred and fifty years (c.1100-1250), during one of the most significant periods of social change in the history of Western civilisation. Yet they remain largely unknown to most English-speaking readers of the twenty-first century. In Heroes of the Old French Epic (Boydell, 2005) Michael Newth translated a selection of the traditional militaristic narratives dominated by male heroes. This oral-based epic genre was increasingly influenced by the ethos of romance, and the present volume offers full English verse translations of six more of these songs, each chosen this time to illustrate the range of roles gradually accorded to women in these originally militaristic narratives. Four key narrative roles have been selected - woman as helpmeet, woman as lover, woman as victim, and woman as spiritual model - in order to illustrate some major changes in the social status of women that took place during the period of this popular genre's existence. These poems are a key witness to the final stages of the chansons de geste before they were overtaken by the new fashion for the fictions of courtly romance. Apart from "The Capture of Orange", which has never been translated into modern English verse, none of the poems have yet appeared in English translation.
PART I -- Saracen Sirens -- The capture of Orange (c. 1150) -- The song of Floovant (c. 1170) -- PART II -- Bartered Brides -- Aye of Avignon (c. 1180) -- Aye of Avignon II (c. 1190) -- PART III -- Martyred Minds -- The song of Blancheflor (c. 1240) -- Bertha Broad-Foot (c. 1270).
Includes bibliographical references (pages 421-422).
Print version record.
JSTOR
Keywords: Chansons de geste -- Translations into English; Epic poetry, French -- Translations into English; Women in literature; Femmes dans la littérature.; LITERARY CRITICISM -- Medieval; Chansons de geste; Epic poetry, French; Women in literature; Translations